Behaviour of Islamic stock market in a prolonged down global market: empirical evidence from Malaysia - Mustafa, Siti Aisyah; Ramlee, Roslily; Kassim, Salina (IIUM Institute of Islamic Banking and Finance, 2015)
By focusing on Malaysian data, this study investigates the response of the Islamic stock market to changes in major macroeconomic variables such as industrial output, money supply, unemployment rate, exchange rate and foreign interest rate. It focuses on the period from January 2010 to December 2014 to capture the period of a prolonged downturn in the global financial market due to the U.S. financial crisis which started in 2007. The study adopts the co-integration approach of the Auto Regressive Distributed Lag (ARDL) model in order to capture the long -run relationship between the variables. The results show that the Islamic stock price reacts positively to the domestic factors, namely industrial activities, money supply, unemployment rate and real effective exchange rate disturbances. Interestingly, it reacts negatively to the foreign interest rate, suggesting investors’ “flight to quality” behaviour during a downturn in the global equity market.